You say it first - Mallery, Susan (Mallery, Susan. Happily Inc., 2017)
Sculptor Nick Mitchell grew up in a family of artists and learned from his volatile father that passion only leads to pain. As he waits on a new commission, he takes a day job as a humble carpenter at a theme wedding venue. The job has its perks--mainly the venue's captivating owner, Pallas Saunders. Although he won't let love consume him, he's all in for ecstasy with an expiration date. Pallas adores Weddings in a Box. But if she can't turn the floundering business around, she'll have no choice but to cave to her domineering mother and trade taffeta for trust funds working at the family's bank. Then when a desperate bride begs Pallas for something completely out of the box, her irresistible new hire inspires her. Nick knows she doesn't belong behind a desk, and she knows in her heart that he's right--where she really belongs is in his arms.